(3cJGH HGddZI GdJQcjIs - (3CHh GdeYGdj ceGd GdOjf MSjf Hf MSf GdMSjfj GdMGFQjs ((3eMeO Hf EHQGgje GdChGdi s)
(3ChdgG (B:s
(3MeO hSGS Ydjei QGfQOcg s
(3BNQgG (B:s
(3bhGad GdBeGd hefGN ShGHd GdCeGd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdeNWhW ecJhH HGddZI GdJQcjIs
(3JedcgG fGSNgG s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdeLGejYs